Need For Mobile Learning: Technologies and Opportunities - Goksu, Idris; Atici, Bunyamin (Elsevier Science Bv, 2013)
Along with the fast developments in mobile technologies, the need to learn mobile learning has become more important. The easy usage and easy accessibility of these mobile devices have made them more significant than ever. This study gains importance in extend of the need for mobile learning and meeting the new learning conditions. In addition, handling the current and the future mobile learning and suggesting some new ideas about it are also considered as important topics. (C) 2013 The Authors. Published by Elsevier Ltd.
13th International Educational Technology Conference -- OCT 30-NOV 01, 2014 -- Lisbon, PORTUGAL
Keywords: mobile learning; mobile devices; mobile technologies; augmented reality